An fMRI Study of the Brain Network Involved in Teeth Tapping in Elderly Adults - Kobayashi, T.; Fukami, H.; Ishikawa, E.; Shibata, K.; Kubota, M.; Kondo, H.; Sahara, Y. (Frontiers in Aging Neuroscience, 2020)
Cortical activity during jaw movement has been investigated using various noninvasive brain imaging methods, but the ways in which orofacial sensory inputs contribute to voluntarily jaw movement remain unclear. In this study, we used functional magnetic resonance imaging (fMRI) to investigate brain activities during a simple teeth tapping task in elderly dentulous (ED) and elderly edentulous subjects who do (EEd) or do not (EE) wear dentures to analyze their functional network connections. 1) A general linear model analysis revealed that teeth tapping induced brain activity at various foci (p < 0.05, family-wise error corrected), including the primary sensory cortex (SI), primary motor cortex (MI), supplementary motor cortex (SMC)/premotor cortex (PMA), insula cortex, cerebellum, thalamus, and basal ganglia in each group. The dorso-lateral part of the prefrontal cortex (DLPFC) was activated in the ED and EEd, but not in the EE groups. 2) Group comparison between the ED and EEd subjects revealed decreased activity in the SI, MI, Brodmann area 6 (BA6), thalamus (ventral posteromedial nucleus, VPM), basal ganglia, and insular cortex (p < 0.05, uncorrected). This suggests that the decreased S1/M1 activity in the EEd group is related to missing teeth, which leads to reduced periodontal afferents. 3) A conjunction analysis among the three groups revealed that teeth tapping commonly activates the SI, MI, BA6, cerebellum, thalamus (VPM), and basal ganglia (putamen) (p < 0.05, FWE corrected). These areas are associated with voluntary movements. 4) Psychophysiological interaction analysis demonstrated that cortical and subcortical structures, such as SI, MI, SMC/PMA, DLPFC, insula cortex, cerebellum, and basal ganglia, are likely to function as hubs and form an integrated network that cooperates in the control of teeth tapping. All of these results suggest that oral sensory inputs are significantly involved in the control of teeth tapping via feedforward control of intended movements as well as feedback control of ongoing movements.